(untitled) (La U Investiga, 2017)
The consumption of fruit juices increases the antioxidant status and is associatedwith high mineral capture. In this sense, the tree tomato (C. betacea) has been proposed as a fruit with high nutraceutical power for its content of vitamins, minerals and phytochemicals. The objective of this work was to determine the modulating effect of tree tomato juice on the concentrations of copper, zinc and magnesium in volunteers classified nutritionally. Fifty (50) volunteers; 42 women and 8 men aged 45 ± 8 years consumed 100ml of tree tomato juice for 45 days. Before of treatment (BF) and after treatment (AT) was finished, the nutritional sta- tus was determined and blood samples were taken for the determination of Cu, Zn and Mg by atomic absorption spectrophotometry. 10% presented Cu values in the reference ranges. 22% of the BF volunteers presented Zn values in reference ranges; increasing significantly by 50% AT. 66% of the volunteers presented Mg values in reference ranges. In AT volunteers with normal weight, overweight and abdominal obesity, Zn increased significantly. The Cu/Zn ratio decreased after the treatment. There was a positive relationship between copper concentrations and age before treatment. The improvement in zinc concentrations and the decrease of the Cu/Zn index is indicative that the consumption of the juice of this fruit can help to reduce processes related to metabolic diseases.